A primary source guide to the United Kingdom - Blomquist, Christopher (New York : PowerKids Press, 2005)
Text and photographs depict the history, government, culture, and traditions of the United Kingdom, the birthplace of the Industrial Revolution.
Includes index.
6.9
3-6
Keywords: Great Britain -- Juvenile literature; Northern Ireland -- Juvenile literature; Great Britain; Northern Ireland; Great Britain; Northern Ireland